If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + -4y = -5 Solving -7x + -4y = -5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. -7x + -4y + 4y = -5 + 4y Combine like terms: -4y + 4y = 0 -7x + 0 = -5 + 4y -7x = -5 + 4y Divide each side by '-7'. x = 0.7142857143 + -0.5714285714y Simplifying x = 0.7142857143 + -0.5714285714y
| 9x+9=4x*29 | | -7x+-4y=5 | | 60=60-5t^2 | | 5b-3-8b-6= | | x=rh+s | | 4x+33=2*(x-8) | | 8x-1=11x-7 | | 9a+6b=0 | | 3x-8(3x-4)=31+6(1-6x)-(3-8x)*2 | | [2y-2]=y | | X*2y=400 | | -17+x=3 | | 4m-9=23 | | -10x+16=6x | | 5k^2-13k+8=0 | | -4.9=5.7+x | | 9(x-1)=6(x+2)-x | | (7x-4)(8x-3)=56x^2-37x+4 | | -2/3w=14 | | 14x-(9x-5)=30 | | Y-12-4x+3=-1 | | 9p=kp-7n | | -1+3/4c=-6 | | 6x-7=2x+4+2 | | 3/2x-2=6 | | 5mn+3mn-1mn= | | 6y-11y=-15-20 | | 2t^4+t^2-1=0 | | 3/10+5x=2/3x-1 | | U-3(x-1)+9=15 | | 12X^2-320X+1200=0 | | 960*x=768*x+(768*12) |